Analisis Resepsi Pelajar SMA dan SMK di Jakarta Timur Mengenai Pelecehan Seksual Kepada Laki-laki dalam Film "Dear David" - Raissa Aristawidya Salsabilla; Dyah Kusumawati (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2026)
Boy who are sexually abused can experience the same effects as other victims of sexual harassment, but they also face some additional barriers because of social attitudes and stereotypes about boy and masculinity. The film Dear David raises the issue of sexual harassment against boy. The purpose of this study is to describe the reception of high school and vocational students in East Jakarta regarding sexual harassment of boy in the film Dear David. This study uses a descriptive qualitative approach with Stuart Hall's encoding and decoding theory, which is analyzed using the audience reception analysis method. Based on the results of in-depth interviews with the five informants who were victims or witnesses of sexual harassment, it showed that the four informants were in a position of dominant hegemony because the four informants had the same understanding of sexual harassment against boy based on their personal experience and testimony. While one other informant was in a negotiating position because the meaning of sexual harassment in the film was described as excessive and not in accordance with his personal experience.